Measuring Embeddedness and Its Effect on New Venture Creation—A Study of Farm Diversification. (26th May 2014) - Ferguson, Richard; Hansson, Helena
<x xml:space="preserve">Abstract</x> Social embeddedness has been found to influence the development of new ventures, providing a basis for the trust needed for economic exchange. This study takes a novel approach to measuring embeddedness, focusing on entrepreneurs' perceived value of advice from various network partners, and shows that different types of partners exercise different influences. Analysis of a survey of 670 farm businesses shows varied embeddedness in professional and social networks, where stronger embeddedness in social networks is more associated with the development of diversified enterprises, whereas stronger professional networks is more associated with a lower incidence of such development. Copyright © 2014 John Wiley & Sons, Ltd.